Dionysos in archaic Greece - Isler-Kerényi, Cornelia (2007)
For the Greek, Dionysos was a very important god: for individuals as well as for the community as a whole. As there are only a few written sources dating from before the 5th Century BC, the many images of Dionysos on Greek vases may well offer a genuine approach to the meaning given by the ancient viewer. This book explores the earliest images followed by those on small vases for private use, on mixing bowls of the symposion, on amphoras, on later drinking cups and on archaic sculptures. It gives an overview of Dionysian iconography of the 5th Century BC as well as an overall interpretation. T.